Writings on the wall : a new equality beyond black and white - Abdul-Jabbar, Kareem, 1947-; Obstfeld, Raymond, 1952- (New York : Time Home Entertainment, Inc., 2016)
Traces the evolution of the author's views on social justice, from his youth in the civil rights era to his current role as a cultural commentator on topics ranging from race and economic inequality to music and the influence of the media.
Keywords: Equality -- United States; Social justice -- United States; Racism -- United States; Discrimination -- United States; Equality -- United States; Social justice -- United States; Racism -- United States; Discrimination -- United States; United States -- Social conditions; United States -- Social conditions